Total and phytoplankton group chlorophyll concentrations from underway spectrophotometry with water mass classification in the East Greenland Sea from Polarstern expeditions 2015-2024 - Bracher, Astrid; Mehdipour, Ehsan; Xi, Hongyan; Zeising, Moritz; Hohe, Christian; von Appen, Wilken-Jon (PANGAEA, 2025)
We present a high spatially resolved (around 300 m) data set on the chlorophyll-a concentrations of all phytoplankton (total chlorophyll-a), diatoms, haptophytes and chlorophytes various phytoplankton pigments (unit: mg/m³) estimated from particulate absorption data derived from underway AC-S measurements operated on eight R/V POLARSTERN expeditions in the Greenland Sea (North of 66.3°N to 82°N within the Atlantic Ocean) between 2015 to 2024: PS93.2, PS99.2, PS107, PS121, PS126, PS131, PS136 and PS143-2. For each data point we further provide the percentage of Atlantic Water and Polar Water and the association into the three regions: East Greenland Sea, Central Fram Strait and West Spitsbergen Current. Mind that the classification of water masses and regions is only valid for the Hausgarten area (78°N to 80°N and 7°W to 15°E). The details of the instrument set-up, the data and the methods are described in Bracher et al. (2025).
Keywords: absorption spectroscopy; chlorophyll-a concentration; Phytoplankton composition; Underway measurement; water mass fraction